Public food procurement from smallholder farmers: Literature review and best practices - Ana Miranda (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
Governments in all parts of the world use their purchasing power to advance social, economic and environmental goals. In a similar vein, public food procurement has also been used to promote a number of positive outcomes. There is growing interest among countries and international institutions in using public food purchases to promote the integration of smallholders into markets and strengthen rural livelihoods. Despite the expansion of public food procurement from smallholder farmers, research into these novel strategies is still limited. This paper will address some of the research gaps by identifying best practices in promoting smallholder participation in public food procurement. It reviews the body of available literature in the field and draws key lessons learned. The findings can assist policymakers in the design and implementation of public food procurement initiatives targeted at smallholders.
Keywords: 330; Public; food; procurement; smallholder; farmers; literature; review; best; practices